2022
DOI: 10.1007/s10964-022-01664-8
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Predictors of Teen Dating Violence Involvement at Age 17

Abstract: The distal relationship between risk factors in childhood and subsequent dating violence in late adolescence has not often been explored using longitudinal data. This study aims to shed light on the problem of dating violence by examining children’s backgrounds at age 7 and the link to the future involvement in dating violence at age 17 using the first and seventh waves of the Zurich Project on the Social Development from Childhood to Adulthood (z-proso, n = 644). The sample consists of 644 multiethnic adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 87 publications
2
12
0
Order By: Relevance
“…Patoari (2020) associated poor educational opportunities for teenagers as a source of their increased desperation because they do not see any way out of the poverty that characterizes their lives at home with their families. This particular socio-economic disadvantage incentivizes criminal behaviour since the teenager finds it one of the quickest financial solutions to escape poverty (Pereda et al, 2022). Uche & Okemini (2022) observed that teenagers who miss out on school or spend more time at home than school are highly susceptive to negative influences in their neighbourhood and are often compelled to join gangs for social and economic survival.…”
Section: Socio-economic Factors Causing Teenage Delinquency In Slumsmentioning
confidence: 99%
See 4 more Smart Citations
“…Patoari (2020) associated poor educational opportunities for teenagers as a source of their increased desperation because they do not see any way out of the poverty that characterizes their lives at home with their families. This particular socio-economic disadvantage incentivizes criminal behaviour since the teenager finds it one of the quickest financial solutions to escape poverty (Pereda et al, 2022). Uche & Okemini (2022) observed that teenagers who miss out on school or spend more time at home than school are highly susceptive to negative influences in their neighbourhood and are often compelled to join gangs for social and economic survival.…”
Section: Socio-economic Factors Causing Teenage Delinquency In Slumsmentioning
confidence: 99%
“…Another key socio-economic factor that is associated with teenage delinquency is family dysfunction. This is characterized by poor or inconsistent parental discipline (Khan, 2016;Pereda et al, 2022), insufficient parental or guardian supervision (Khan, 2016;Tiwari et al, 2023), and maternal rejection (Patoari, 2020). According to Javed et al (2012), family dysfunction is also characterized by parental criminality, which in turn inspires teenagers to engage in criminal behaviour.…”
Section: Socio-economic Factors Causing Teenage Delinquency In Slumsmentioning
confidence: 99%
See 3 more Smart Citations